2020
DOI: 10.3390/jcm10010033
|View full text |Cite
|
Sign up to set email alerts
|

Early Orthodontic Treatments of Unilateral Posterior Crossbite: A Systematic Review

Abstract: We aimed to report an update of the systematic review by Petrén et al. (2003). The objective was to evaluate how orthodontic treatments can affect unilateral posterior crossbite (UPXB) in primary and early mixed dentition. Several databases were consulted, and articles published between January 2002 and March 2020 were selected. This review examines the following studies: randomized clinical trials, prospective and retrospective studies with concurrent untreated or normal control groups, and clinical trials co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…It has also been observed that ↕ [57,61,80] Maximal clench NA ↕ [61,64,81] = [76][38,54,56,62] NA NA certain types of malocclusions such as UPXB could have a greater impact on normal jaw function than other types of malocclusions. Posterior crossbite is a common malocclusion affecting approximately 8% to 22% of orthodontic patients in the primary and early mixed dentition, with approximately 50% of cases being unilateral posterior crossbite (i.e., UPXB) [90,91]. Apart from faulty dental occlusion, children with UPXB often suffer from a morphological asymmetry of the mandible [52,92] or bilateral differences in masticatory muscle thickness [93].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that ↕ [57,61,80] Maximal clench NA ↕ [61,64,81] = [76][38,54,56,62] NA NA certain types of malocclusions such as UPXB could have a greater impact on normal jaw function than other types of malocclusions. Posterior crossbite is a common malocclusion affecting approximately 8% to 22% of orthodontic patients in the primary and early mixed dentition, with approximately 50% of cases being unilateral posterior crossbite (i.e., UPXB) [90,91]. Apart from faulty dental occlusion, children with UPXB often suffer from a morphological asymmetry of the mandible [52,92] or bilateral differences in masticatory muscle thickness [93].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are several studies that used 2D radiographs and dental casts to evaluate and measure the structural changes produced by RME [2,3,6,7,[18][19][20]. Some authors studied these effects using 3D technologies when the first permanent molars were used as anchorage [17,21,22], also comparing tooth-borne and tooth tissue-borne appliances [2,9,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral posterior crossbite is a malocclusion disease characterized by an inverse relationship between the lower and upper dental cusps [1,[13][14][15][16]. Electrophysiological studies have demonstrated that, when chewing on the affected side, the ipsilateral muscle shows reduced activity and the contralateral muscle activity is normal or increased [2,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%